Endothelial Nitric Oxide Synthase (eNOS) Gene Polymorphism is Associated with Age Onset of Menarche in Sickle Cell Disease Females of India - Sudhansu Sekhar Nishank (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Objective :  Females with sickle cell disease (SCD) often show late onset of menarche. In transgenic sickle cell mouse, deficiency of gene encoding endothelial nitric oxide synthase (eNOS) has been reported to be associated with late onset of menarche. Thus to explore the possible association of eNOS gene polymorphism with age of onset of menarche in SCD females, 3 important eNOS gene polymorphisms- eNOS 4a/b, eNOS 894G>T (rs1799983) and eNOS-786 T>C (rs2070744) and plasma nitrite levels were tested among three groups of females- SCD late menarche, SCD early menarche and control females.